2012
DOI: 10.1016/j.otpol.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Nasal obstruction as a key symptom in allergic rhinitis: efficacy and safety of a medical device in children

Abstract: Allergic rhinitis (AR) is a global health problem that has increased rapidly in prevalence over the past few decades. Nasal congestion, which represents a cardinal symptom of AR, appears to be difficult to treat and, especially for pediatric population, therapies that are both well tolerated and effective in relieving nasal congestion are needed. The aim of the present study was to evaluate the safety and clinical effectiveness of the medical device (lactoferrin, carboximetil β-glucan, D-panthenol, dipotassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…16 Both the anti-inflammatory and cleansing action seem to restore the "cytological architecture" of the nasal mucosa. 17,18 In a comparative study, Mansi et al observed a similar benefit of intranasal glycyrrhizin and mannitol and intranasal corticosteroid in reducing nasal congestion. 6 Nasal corticosteroids are currently the first therapeutic choice in chronic rhinopathies.…”
Section: Discussionmentioning
confidence: 95%
“…16 Both the anti-inflammatory and cleansing action seem to restore the "cytological architecture" of the nasal mucosa. 17,18 In a comparative study, Mansi et al observed a similar benefit of intranasal glycyrrhizin and mannitol and intranasal corticosteroid in reducing nasal congestion. 6 Nasal corticosteroids are currently the first therapeutic choice in chronic rhinopathies.…”
Section: Discussionmentioning
confidence: 95%
“…Two studies by Passali et al investigated the effects of a nasal spray containing dexpanthenol for the treatment of allergic rhinitis in children for periods of 4 weeks and 2 weeks, respectively [ 36 , 37 ]. They studied 100 children in one trial and 50 children in the other trial.…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by tilting the T cell balance towards a Th1 phenotype out of the allergic Th2 and Th17 ones [ 131 ]. Studies on humans showed the efficacy of a multicomponent device containing LF in children, improving AR symptoms evaluated with a Visual Analogue scale and objectivated through Active Anterior Rhinomanometry and Mucociliary Transport Time [ 142 , 143 ]. The clinical application of LF may also be helpful in the diagnosis of AR; as mentioned previously, it has been proposed that LF might serve as an early detection biomarker, given that the combination of serum LF concentration and antigen-specific IgE levels can predict the condition with a suitable sensitivity and specificity [ 81 ].…”
Section: Lactoferrin Clinical Application In Allergic Airway Diseasesmentioning
confidence: 99%
“…The proposed actions of LF could benefit from a systemic approach, as this protein impacts a variety of metabolic and regulatory pathways, particularly meriting further examination in paediatric applications. Only the two reported studies evaluated the efficacy of LF administration in AR in children, but it is associated with other components [ 142 , 143 ]. Our manual research has found a patent application and a phase II clinical trial for its use in asthma.…”
Section: Lactoferrin Clinical Application In Allergic Airway Diseasesmentioning
confidence: 99%